2013
DOI: 10.1089/neu.2013.3001
|View full text |Cite
|
Sign up to set email alerts
|

Ethosuximide and Phenytoin Dose-Dependently Attenuate Acute Nonconvulsive Seizures after Traumatic Brain Injury in Rats

Abstract: Acute seizures frequently occur following severe traumatic brain injury (TBI) and have been associated with poor patient prognosis. Silent or nonconvulsive seizures (NCS) manifest in the absence of motor convulsion, can only be detected via continuous electroencephalographic (EEG) recordings, and are often unidentified and untreated. Identification of effective anti-epileptic drugs (AED) against post-traumatic NCS remains crucial to improve neurological outcome. Here, we assessed the anti-seizure profile of et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Topiramate, yet another anticonvulsant, is currently being studied in the PEPTO trial to compare it to PHT in preventing epilepsy after TBI. Recent evidence demonstrates ethosuximide, another anti-convulsant, as capable of decreasing the incidence, frequency, and delaying the onset of non-convulsive seizures in rats suffering a penetrating ballistic-like brain injury [ 179 ]. However, ethosuximide treatment has not been attempted in the clinical arena ( Table 5 ).…”
Section: Seizure Treatmentsmentioning
confidence: 99%
“…Topiramate, yet another anticonvulsant, is currently being studied in the PEPTO trial to compare it to PHT in preventing epilepsy after TBI. Recent evidence demonstrates ethosuximide, another anti-convulsant, as capable of decreasing the incidence, frequency, and delaying the onset of non-convulsive seizures in rats suffering a penetrating ballistic-like brain injury [ 179 ]. However, ethosuximide treatment has not been attempted in the clinical arena ( Table 5 ).…”
Section: Seizure Treatmentsmentioning
confidence: 99%
“…According to Dash et al ( 84 ), the administration of valproate starting at 30 min or 3 h after CCI promoted improvement of blood-brain barrier (BBB) integrity, decrease of hippocampal dendritic damage, improved spatial memory and motor function, and lessened cortical contusion volume. High doses of ethosuximide and phenytoin administered 30 min after penetrating ballistic-like brain injury attenuated spontaneous non-convulsive seizures, but lower doses failed to have the same effect ( 85 ). The clinical relevance of such findings, however, is hampered by the extremely short time interval between injury and drug administration.…”
Section: Antiepileptic Drugs (Aeds)mentioning
confidence: 99%
“…Chronic spontaneous seizures were reported after FP-and CCIinduced TBI, both in rats and mice. Acute epileptiform activity/seizures (up to 3 days after injury) has been reported in a rat model of penetrating ballistic injury [28][29][30][31] and blast injury [32], but whether late spontaneous seizures develop after these injury mechanisms remains to be studied. So far, studies have not found acute/late seizures after repeated mild concussive TBI [33].…”
Section: Process Of Epileptogenesis In Experimental Modelsmentioning
confidence: 99%